A novel energy-effective and carbon-emission reducing mortars with bottom ash and phase change material: Physico-mechanical and thermal energy storage characteristics - Gencel, Osman; Hekimoglu, Gokhan; Sari, Ahmet; Sutcu, Mucahit; Er, Yusuf; Ustaoglu, Abid (Elsevier, 2021)
Novel cement based mortars containing bottom ash (BA) and phase change material (PCM) as thermal energy storing material were developed for thermal controlling of buildings. Form-stable BA/Capric-Stearic (C-S) acid eutectic mixture composite was produced at an impregnation rate of 30 wt% C-S. Melting temperature and latent heat capacity of form-stable composite PCM were observed as 23.65 degrees C and 52 J/g, respectively while the mortar containing 30 wt.% composite PCM had a melting temperature of 21.42 degrees C and latent heat value of 13.62 J/g. Water demand, porosity and absorption was increased depending on the variation of BA/C-S composite PCM. The compressive strength and dry unit weight of the mortar decreased up to 35 MPa at 28th day and 1826 kg/m(3). The highest indoor heat difference between reference mortar and BA/C-S composite included-mortar was found to be 2.80 degrees C for heating and 1.95 degrees C for cooling period. Analytical approaches revealed that composite PCM adapted buildings have promising annual energy saving and carbon-emission reducing potential for various fuels. It was concluded that usage of the developed composite PCM has high potential for creation novel kinds of energy saving panels, concretes, mortars, bricks etc. used for inside temperature regulation of buildings.
Keywords: Bottom ash; Phase change material; Cementitious mortar; Thermal energy storage; Energy saving; Carbon emission reducing